2012
DOI: 10.23986/afsci.5016
|View full text |Cite
|
Sign up to set email alerts
|

Dairy cow excreta patches change the boreal grass swards from sink to source of methane

Abstract: We studied the annual methane (CH 4 ) flux rates from experimental excreta patches on a boreal dairy pasture in Eastern Finland. The CH 4 fluxes were measured with a chamber technique during snow free seasons and with gas gradient technique during winter from timothy-meadow fescue sward with mineral N fertilization (220 kg ha -1) and from grass-white clover mixture without mineral N addition. The simulated dung and urine patches were applied in June or August two consecutive grazing seasons. The measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Absolute flux rates of CO 2 , CH 4 and N 2 O in chambers with dung were observed to be high compared to emissions from agricultural soils in general [4], [11], [12], [33] – and compared to the fluxes observed in our control chambers without dung. However, the elevated fluxes from individual pats were of relatively short duration (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Absolute flux rates of CO 2 , CH 4 and N 2 O in chambers with dung were observed to be high compared to emissions from agricultural soils in general [4], [11], [12], [33] – and compared to the fluxes observed in our control chambers without dung. However, the elevated fluxes from individual pats were of relatively short duration (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…These studies also found significant fluxes of CO 2 , CH 4 and N 2 O from dung (e.g. [5], [9], [10], [12], [33]). CH 4 emissions from the dung of grazing dairy cows have been observed to be particularly high, ranging from 300 to 2040 mg CH 4 m −2 over the first ten days [4].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Therefore the soil fluxes referred to here are the combination of fluxes from the soil microbial community and fluxes from dung/urine which normally dominate the pure soil fluxes (Flessa et al, 1996). Emissions from cattle dung were estimated to be 0.778 g CH 4 head −1 d −1 (Flessa et al, 1996) and from Finnish dairy cows to 470 g CH 4 ha −1 over a 110 day grazing period (Maljanen et al, 2012). The soil flux in the present study (16 g ha −1 d −1 ) is around 3 times higher than the corresponding flux calculated with the literature numbers (Flessa et al (1996): 5 g ha −1 d −1 and Maljanen et al (2013): 4.3 g ha −1 d −1 ).…”
Section: Flux Data Availability and Selectionmentioning
confidence: 99%